Features of a mobile health intervention to manage chronic obstructive pulmonary disease: a qualitative study. (September 2020) - Alwashmi, Meshari F.; Fitzpatrick, Beverly; Davis, Erin; Farrell, Jamie; Gamble, John-Michael; Hawboldt, John
Background: The use of mobile health (mHealth) interventions has the potential to enhance chronic obstructive pulmonary disease (COPD) treatment outcomes. Further research is needed to determine which mHealth features are required to potentially enhance COPD self-management. Aim: The aim of this study was to explore the potential features of an mHealth intervention for COPD management with healthcare providers (HCPs) and patients with COPD. It could inform the development and successful implementation of mHealth interventions for COPD management. Methods: This was a qualitative study. We conducted semi-structured individual interviews with HCPs, including nurses, pharmacists and physicians who work directly with patients with COPD. Interviews were also conducted with a diverse sample of patients with COPD. Interview topics included demographics, mHealth usage, the potential use of medical devices and recommendations for features that would enhance an mHealth intervention for COPD management. Results: A total of 40 people, including nurses, physicians and pharmacists, participated. The main recommendations for the proposed mHealth intervention were categorised into two categories: patient interface and HCP interface. The prevalent features suggested for the patient interface include educating patients, collecting baseline data, collecting subjective data, collecting objective data via compatible medical devices, providing a digital action plan, allowing patients to track their progress, enabling family members to access the mHealth intervention, tailoring the features based on the patient's unique needs, reminding patients about critical management tasks and rewarding patients for their positive behaviours. The most common features of the HCP interface include allowing HCPs to track their patients' progress, allowing HCPs to communicate with their patients, educating HCPs and rewarding HCPs. Conclusion: This study identifies important potential features so that the most effective, efficient and feasible mHealth intervention can be developed to improve the management of COPD. The reviews of this paper are available via the supplemental material section.